2019
DOI: 10.1089/g4h.2018.0145
|View full text |Cite
|
Sign up to set email alerts
|

Changing Stress Mindset Through Stressjam: A Virtual Reality Game Using Biofeedback

Abstract: Objective: A range of recent studies suggest that overall mindset about stress is related to health, performance, and well-being. Therefore, an exploratory study was conducted to examine whether virtual reality (VR) with real-time biofeedback would have potential in training people in an engaging way to develop a new stress-is-enhancing mindset.Materials and Methods: The specific application to improve people's stress mindset that was used in this study is Stressjam. The application was tested on its attractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…This type of game is often defined in the literature as a “serious game” [ 69 ], as gaming features are used as the primary medium for serious purposes [ 66 ]. Several custom-made video games for relaxation integrate biofeedback techniques into the game modes, such as Deep [ 70 , 71 ], Nevermind [ 72 ], MindLight [ 73 , 74 ], Dojo [ 75 , 76 ], and StressJam [ 77 ]. Furthermore, studies have shown that ad hoc video games could help adults with anxiety better handle emotional and physiological responses to stressors [ 78 ] and improve behavioral performance on anxiety-related stress tasks [ 79 ].…”
Section: Introductionmentioning
confidence: 99%
“…This type of game is often defined in the literature as a “serious game” [ 69 ], as gaming features are used as the primary medium for serious purposes [ 66 ]. Several custom-made video games for relaxation integrate biofeedback techniques into the game modes, such as Deep [ 70 , 71 ], Nevermind [ 72 ], MindLight [ 73 , 74 ], Dojo [ 75 , 76 ], and StressJam [ 77 ]. Furthermore, studies have shown that ad hoc video games could help adults with anxiety better handle emotional and physiological responses to stressors [ 78 ] and improve behavioral performance on anxiety-related stress tasks [ 79 ].…”
Section: Introductionmentioning
confidence: 99%
“…Supporting a positive effect of combining biofeedback and VR on user engagement and immersion is its increased usage in game design. For example, in the biofeedback-integrated VR applications StressJam and Breath VR users must modify their heartrate and breathing actions, respectively to interact with element of the gaming environment and direct gameplay [ 35 , 36 ]. Like Performance Edge VR, the relaxation-focused VR game DEEP incorporates respiratory biofeedback to support diaphragmatic breathing at a slow and steady rate [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…meditation), rather than specific skills training [33]. Several VR applications have integrated biofeedback including heart and breathing rate into a virtual environment [34][35][36][37][38], with reported improvements in user engagement and motivation. To date, these applications have not integrated respiratory biofeedback into a structured skills training program for a military audience.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Maarsingh et al examined whether VR with real-time biofeedback would help in training people to develop a new mindset related to stress. They concluded that using a VR application may be useful in working toward a more positive stress mindset [ 48 ].…”
Section: Discussionmentioning
confidence: 99%